Historical trends leading to the same-sex marriage law in Argentina - Pablo Ben; Santiago Joaquín Insausti (Cahiers des Amériques Latines, 2021)
This article analyzes the social transformations converging in “the revolution of LGBT rights” in Argentina. Unlike other short-term perspectives focusing on the strategies of LGBT organizations and on sudden and recent shifts in politics, our study concentrates on the historical transformations of varying length that established the conditions under which the struggle for same-sex marriage could succeed. Among other trends, we will analyze the changes in family structure, the relation between same-sex marriage and Argentine national identity at the end of the 19th century, the decline of religion, and the transformation of male homosexual subculture over the four decades prior to 2010 when same sex marriage was passed.